2015
DOI: 10.1073/pnas.1508760112
|View full text |Cite
|
Sign up to set email alerts
|

HAX-1 regulates cyclophilin-D levels and mitochondria permeability transition pore in the heart

Abstract: The major underpinning of massive cell death associated with myocardial infarction involves opening of the mitochondrial permeability transition pore (mPTP), resulting in disruption of mitochondria membrane integrity and programmed necrosis. Studies in human lymphocytes suggested that the hematopoietic-substrate-1 associated protein X-1 (HAX-1) is linked to regulation of mitochondrial membrane function, but its role in controlling mPTP activity remains obscure. Herein we used models with altered HAX-1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 35 publications
(64 reference statements)
5
71
0
Order By: Relevance
“…We have shown here an evidence that Hax1 inhibits ER stress-induced downregulation of MFN1 and MFN2 mRNA. Moreover, this study is in agreement with previous findings which demonstrated that Hax1 protects from mitochondrial membrane depolarization [57]. This is important because loss of MFN1 or MFN2 could render the mitochondria more susceptible to lose their membrane potential [65].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have shown here an evidence that Hax1 inhibits ER stress-induced downregulation of MFN1 and MFN2 mRNA. Moreover, this study is in agreement with previous findings which demonstrated that Hax1 protects from mitochondrial membrane depolarization [57]. This is important because loss of MFN1 or MFN2 could render the mitochondria more susceptible to lose their membrane potential [65].…”
Section: Discussionsupporting
confidence: 92%
“…Hax1 has been recently shown to suppress apoptosis in various models including cardiac cells, both in vitro and in vivo [24, 25, 27, 31, 57, 58]. Moreover, Hax1 may regulate many unrelated molecules, indicating its contribution to diverse signaling mechanisms within the cell [23, 5760]. Given the crucial pro-death role of ER stress in the diseased heart, it is essential to dissect different preferential apoptotic pathways triggered by this mechanism in different cardiac cell models.…”
Section: Discussionmentioning
confidence: 99%
“…CypD and TSPO are potent components that act as regulators of MPTP opening . Down‐regulation of CypD prevents MPTP opening and protects against the loss of ΔΨm . Conversely, the loss function of TSPO causes MPTP opening and leads to a reduced ΔΨm .…”
Section: Discussionmentioning
confidence: 99%
“…21,34 Down-regulation of CypD prevents MPTP opening and protects against the loss of ΔΨm. 35 Conversely, the loss function of TSPO causes MPTP opening and leads to a reduced ΔΨm. 21,36 Our results showed that both CypD and TSPO could be poly-ADP-ribosylated, but the effects of this modification on the functions of CypD and TSPO were not studied.…”
Section: Mitophagy Inhibition Due To Knockdown Ofmentioning
confidence: 99%
“…demonstrates that a newly identified partner of Hsp90, the hematopoietic-substrate-1 associated protein x-1 (HAX-1) is involved in the regulation of CypD in the heart. HAX-1 binds to CypD and interfere its binding to Hsp-90, rendering CypD ubiquitination and degradation, resulting in protection against MPTP opening and cell death[49]. …”
Section: Mitochondria Bcl2 Family and Cell Deathmentioning
confidence: 99%